Processo de cicatrização em modelo experimental de queimadura de segundo grau tratada com membranas de borracha natural e própolis - Krupp, Tamires (2018)
Burns are extremely aggressive injuries that can cause physical and psychological trauma to the patient. The fact that there is no dressing with all the ideal characteristics for the treatment of this type of lesion results in the need of new studies that seek to optimize the cicatrization process. Physical-chemical characteristics of the biomembranes of natural rubber and propolis, developed in previous studies of the research group, suggest that they may be appropriate as curatives. In view of this, this work aims to evaluate the healing action of natural rubber membrane and aqueous propolis extract in the burn processes in animal models. For this, 30 Wistar rats (Rattus norvegicus) were used. The animals were divided into six groups, according to the treatment: without treatment (ST); ointment (SP); natural rubber membranes polymerized at 27 °C (BN27 °C); natural rubber membrane and 10% aqueous extract of propolis polymerized at 27ºC (BNEP27ºC); natural rubber membranes polymerized at 60 °C (BN60 °C); natural rubber membrane and 10% aqueous extract of propolis polymerized at 60 °C (BNEP60 °C). The proposed treatments were initiated immediately after induction of the lesion (deep second degree burn) and kept in the animal for 10 days. After this period, the lesions were analyzed macroscopically, the animals were killed by decapitation under deep anesthesia, and biopsies of the skin tissue were removed: the healing wound, the wound border and part of the skin adjacent to the edge of the wound. wound. The removed material was processed and submitted to staining: hematoxylin-eosin and Masson's trichrome. Macroscopic analysis showed that all groups presented crust formation. When evaluating the final areas of the lesions, it was observed that the treatments with membranes polymerized at 60ºC presented a higher percentage of contraction. Histological analysis indicated that silver sulfadiazine and membranes containing natural rubber and aqueous propolis extract presented a reepithelization process, characterized by the detachment of the crust and formation of the epithelium. However, the groups treated with membranes produced only from natural rubber at both polymerization temperatures did not show re-epithelization. Therefore, the data obtained suggest that natural rubber membranes and aqueous propolis extract have properties capable of influencing the healing process of deep second-degree burns.